A new species of Crocus (Iridaceae) from southern Albania (SW Balkan Peninsula) - Miljković, Milica; Ranđelović, Vladimir; Harpke, Dörte (Phytotaxa, 2016)
A new Crocus species (Iridaceae) for southern Albania, Crocus novicii sp. nov. (Iridaceae), is described and illustrated. We here provide diagnostic morphological characteristics, results of molecular analyses, detailed descriptions and illustrations of this new species and compare it with its relatives C. jablanicensis, C. cvijicii and C. veluchensis. Our molecular analysis is based on two chloroplast (matK–trnK, rps16–trnQ) and three nuclear markers (nrETS, nrITS, TOPO6B exon3–exon6) and includes representatives of all related species (C. cvijicii, C. dalmaticus, C. jablanicensis, C. rujanensis, C. sieberi subsp. atticus, and C. veluchensis). Morphologically, C. novicii can be distinguished from its relatives by its white flower with lilac coloring at the base of the perigone and its higher number of leaves (> 3). Although it is morphologically close to C. jablanicensis, molecular analysis has revealed a close affiliation to C. veluchensis. Crocus novicii is diploid with 2n = 20 chromosomes. The new species is named after the Serbian botanist Novica Ranđelović to honor his important work on the genus Crocus on the Balkan Peninsula.